Pelatihan Public Speaking Basic Kepada Siswa Kelas VI MI dan SD Di Desa Gedungan Kabupaten Sumenep Melalui Metode Demonstrasi - Sutrisno, Tri; Lestari, Leli; Septiana, Nanda; Nursobah, Ahmad (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2021)
The ability to speak in public is a skill that must be nurtured, trained and developed from an early age. Especially with the development of the era which is increasingly rapidly demanding the ability to speak with the art of communication that is not rigid, it also determines success in the current era of competition. Even in all life settings speaking becomes a consumption of the surrounding community, while all will give an assessment of the speaker of the voice. Especially for those who are currently studying, speaking and communicating both individually and in groups is currently a trend in learning models. Students who lack opinion, comment, and have not been able to present their work are not the outcame of graduates in the current curriculum. So it becomes important, public speaking skills to be taught, trained and given to children since elementary school. The Service Team from the PGMI Study Program, Tarbiyah Faculty, IAIN Madura, tries to do community service as a form of realization of one of the Tri Dharma of Higher Education. The field of study and training focuses on basic public speaking training for two days in Gedungan Village, Sumenep District. Based on the analysis of the training carried out, the following were found; 1) found a difference between the pre-test and post-test abilities of the participants, when the pre-test participants answered incorrectly as much as 24%, while the post-test experienced an increase in correct answers to 91%, 2) it was also found that the value of speaking practice skills performed by the participants on the second day namely 45% of their performances are good while 13% are still lacking, but this achievement with all the limitations is quite satisfying, 3) the final findings of the event regarding their response to this training, it turns out that 80% of the participants think the training is important, satisfying and activities to be carried out.